2006
DOI: 10.2164/jandrol.106.000281
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Testosterone Undecanoate Injected Alone or in Combination With Norethisterone Enanthate in Healthy Men

Abstract: Long-acting injectable testosterone undecanoate (TU) is a promising androgen for male hormonal contraception. As a prerequisite for a planned multicenter male contraceptive efficacy study, we studied the pharmacokinetics of 2 doses of TU alone or in combination with norethisterone enanthate (NETE) in a prospective 2-center study, randomized for TU dose in each center. Twenty healthy male volunteers in each center were administered intramuscular injections of 750 or 1000 mg TU alone or in combination with 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 49 publications
0
42
0
1
Order By: Relevance
“…The data showed that the interference was negligible and not clinically significant. The only exception was at a DHT concentration of 0.0067 nmol/L, for which the addition of 34 nmol/L T (i.e., 5000-fold more T than DHT) caused a 33.4% increase in the measured DHT concentration, which could be due to the imprecision of measurement at such a low DHT concentration or to interference by the very high relative T concentration. We evaluated the potential for chemical interference by over-the-counter drugs and by additives used in blood-collection tubes.…”
Section: Interference Ion-suppression and Stability Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…The data showed that the interference was negligible and not clinically significant. The only exception was at a DHT concentration of 0.0067 nmol/L, for which the addition of 34 nmol/L T (i.e., 5000-fold more T than DHT) caused a 33.4% increase in the measured DHT concentration, which could be due to the imprecision of measurement at such a low DHT concentration or to interference by the very high relative T concentration. We evaluated the potential for chemical interference by over-the-counter drugs and by additives used in blood-collection tubes.…”
Section: Interference Ion-suppression and Stability Studiesmentioning
confidence: 96%
“…T analysis by RIA was performed with a Coat-A-Count kit from Diagnostic Products Corporation (12,34 ). The DHT RIA was performed with a kit from Diagnostic Systems Laboratories as previously described (21 ).…”
Section: Riamentioning
confidence: 99%
“…The lower limit of quantification for testosterone was 2 ng/dL (0.069 nmol/L). FT represents the unbound, biologically available testosterone and was measured by equilibrium dialysis using labeled testosterone as described previously (44). Serum E1 and E2 concentrations for all mothers were measured with a validated LC-MS/MS method.…”
Section: Serum Hormone Measurementsmentioning
confidence: 99%
“…In fact, the new reference values may not be reflective of the 'global' population, as they fail to include representatives of three continents inhabited by millions of fertile men: Asia, South America and Africa. Moreover, in evaluating morphology, the reference studies included in the WHO 2010 guideline resorted to various methods, including both Tygerberg 'strict' criteria and the David classification system (Meriggiola et al, 1996(Meriggiola et al, , 2003(Meriggiola et al, , 2005Bonde et al, 1998;Buchter et al, 1999;McLachlan et al, 2000;Auger et al, 2001;Guzick et al, 2001;Jensen et al, 2001Slama et al, 2002;Gonzalo et al, 2002;Swan et al, 2003;Turner et al, 2003;von Eckardstein et al, 2003;Brady et al, 2004;Brady et al, 2006;Haugen et al, 2006;Qoubaitary et al, 2006;Wang et al, 2006). Another issue with this new edition relates to the fact that the reference studies used only one single ejaculate to characterize each man, despite the significant biological In no cases was the P-value statistically significant when any of the three groups were compared for each parameter.…”
Section: Discussionmentioning
confidence: 99%